SKARNS OF THE GUMESHEVSK SKARN-PORPHYRY COPPER DEPOSIT, CENTRAL URALS - Grabezhev A.I. (My University, 2004)
The Gumeshevsk copper skarn deposit, which is known from the early 18th century thanks for its high-quality malachite, is located in the eastern, marginal part of the Tagil volcanic zone in the Central Urals. The deposit is paragenetically related to a small D 1-2 quartz diorite intrusion of island-arc type. A distinctive feature of the deposit is the wide occurrence of primary epidote-bearing skarn columns. The bimetasomatic column can be presented in the following generalized scheme: granitoid - amphibole epidosite - amphibole epidote-garnet endoskarn (often with pyroxene) - actinolite garnet exoskarn (sometimes with pyroxene) - marble. The skarns developed at relatively low temperatures (330-380°C, according to the epidote-garnet thermometer). All minerals display a clearly pronounced tendency of their Fe mole fraction to increase from the epidosites to exoskarns, perhaps, owing to an increase in the Fe activity in the fluid in this direction. Minerals often had not attained equilibrium with one another in the outer portions of the endoskarn columns. A significant role in the skarn process was played by the redistribution of Si and Ca of the pristine rocks at the active introduction of Fe and removal of alkalis. The epidosites and exoskarns are insignificantly enriched in Al, whose small amounts were removed from the epidote-garnet zone of the endoskarn columns. The rocks are characterized by widespread retrograde alterations, including CO 2 metasomatism and potassic acid leaching of the granitoids. The sulfur is supposedly of juvenile provenance (the sulfides have δ 34S = 0 ± 2%), while the carbon dioxide was juvenile and local (the carbonate has δ 18O from +12.5 to +19.2% and δ 13C from -2.7 to +0.7%). The zoning of the skarns and the character of their retrograde alterations at the deposit are significantly different from those at ore fields of the copper-magnetite skarn type in the Urals.